PENATALAKSANAAN PERAWATAN FRAKTUR TEMPOROMANDIBULAR JOINT PADA ANAK-ANAK - Budi Yuwono (Fakultas Kedokteran Gigi Universitas Jember, 2010)
The management of temporomandibular joint fracture ocurry in children should be conducted in a high acurracy prucedure, early diagnosis, and good clinical as well as radiograph examinations willhinder unwanted dentofacial development which leads to the disturbance in not only mastication, nor phonetic but also in children aestethic.